2011
DOI: 10.1117/1.3549700
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic investigation of spinal cord injury in a rat model

Abstract: Abstract. Raman spectroscopy was used to study temporal molecular changes associated with spinal cord injury (SCI) in a rat model. Raman spectra of saline-perfused, injured, and healthy rat spinal cords were obtained and compared. Two injury models, a lateral hemisection and a moderate contusion were investigated. The net fluorescence and the Raman spectra showed clear differences between the injured and healthy spinal cords. Based on extensive histological and biochemical characterization of SCI available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Subtracting spectra of one group from spectra of another can reveal which features show differences. This method was used by Saxena et al to identify changes associated with spinal cord injury [469] and by Bai et al to measure senescence in stem cells [470].…”
Section: Direct Peak Analysismentioning
confidence: 99%
“…Subtracting spectra of one group from spectra of another can reveal which features show differences. This method was used by Saxena et al to identify changes associated with spinal cord injury [469] and by Bai et al to measure senescence in stem cells [470].…”
Section: Direct Peak Analysismentioning
confidence: 99%
“…In [6], the use of RS for the identification of spinal nerves in operations of minimally invasive spinal surgery is described, based on quantitative spectral analysis of the main components: proteins, lipids, and DNA. The results confirmed the possibility of identification of the spinal cord and spinal nerve with the help of RS.…”
Section: Physbiosymp17mentioning
confidence: 99%
“…At present, the quality of bioimplants can be assessed in vitro using a set of morphological, morphometric, biochemical and optical methods of investigation, including Raman spectroscopy [4,6].…”
Section: Physbiosymp17mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Saxena et al explored the possibility of using RS to study demyelination and chondroitin sulfate proteoglycans upregulation after SCI. 7 Ruberto et al demonstrated that Raman spectra of an SCI can be observed using an organotypic model. 8 Galli et al assessed the ability of Fourier transform infrared spectroscopy and spontaneous RS to generate contrast data between normal and altered regions on the molecular level in an SCI rat model.…”
Section: Introductionmentioning
confidence: 99%